Recovery and stress monitoring in elite ice hockey: A longitudinal pilot-study - Patrick Eggenberger; Nadine Buffat; Thomas Weber; Raphael Gubler; Emanuel Brunner (Bern Open Publishing, 2024)
Introduction Young athletes in high-level sports experience a greater risk for injury and illness during phases of increased training and competitive load. When recovery is too sparse under these circumstances, psychological and physical health problems could emerge. These are referred to as nonfunctional overreaching or overtraining syndrome, OTS (Daly et al., 2022; Jones et al., 2017; Kiely, 2018). OTS is typically characterized by a reduction in athletic performance that lasts for several weeks to months, accompanied with mood and sleep disturbances, feelings of depression, respiratory tract infections, weight loss, and other symptoms. The prevalence of this condition is high with approxymately 10-20 % of young adult and about 29 % of young athletes from various sports beeing affected (Matos et al., 2011). To our knowledge, no scientifically valid and reliable measurement system currently exists, which would allow the preventive, early diagnosis of overreaching states that might lead to OTS (Weakley et al., 2022). The aim of this study is to develop and evaluate a multiparameter measurement system to assess the recovery and stress state of high-level athletes. Methods Twenty-five male ice hockey players from the highest level Swiss leagues at their respective age group participated (i.e., National League, NL, n = 11, age = 24.8 ± 4.1 years and U20, n = 14, age = 18.5 ± 1.5 years). Over 5-10 weeks during the in-season (i.e., competition phase) measurements were performed on 10 separate days, either after 1 day of passive recovery (T1) or after a day with match/intensive training (T2). The measurement battery included counter movement jump (CMJ), heart rate variability (HRV), executive functions (EF), tympanic temperature (Temp), and Stress Recovery Short Scale (SRSS). Results Independent Student's t-tests showed significant differences (p < 0.05) between timepoints T1 and T2 for CMJ (peak power per body mass), HRV (sympathic and parasympatic indexes), and SRSS (recovery, stress, total score); but not for CMJ (jump height), EF and Temp. Discussion/Conclusion We conclude that various measurment parameters, including CMJ performance, HRV indices, and subjective ratings of recovery and stress could provide valuable feedback for athletes, coaches, and medical staff regarding a potential overreaching or OTS state. References Daly, E., Pearce, A. J., Esser, P., & Ryan, L. (2022). Evaluating the relationship between neurological function, neuromuscular fatigue, and subjective performance measures in professional rugby union players. Frontiers in Sports and Active Living, 4, Article 1058326. https://doi.org/10.3389/fspor.2022.1058326 Jones, C. M., Griffiths, P. C., & Mellalieu, S. D. (2017). Training load and fatigue marker associations with injury and illness: A systematic review of longitudinal studies. Sports Medicine, 47(5), 943-974. https://doi.org/10.1007/s40279-016-0619-5 Kiely, J. (2018). Periodization theory: Confronting an inconvenient truth. Sports Medicine, 48(4), 753-764. https://doi.org/10.1007/s40279-017-0823-y Matos, N. F., Winsley, R. J., & Williams, C. A. (2011). Prevalence of nonfunctional overreaching/overtraining in young English athletes. Medicine & Science in Sports & Exercise, 43(7), 1287-1294. https://doi.org/10.1249/MSS.0b013e318207f87b Weakley, J., Halson, S. L., & Mujika, I. (2022). Overtraining syndrome symptoms and diagnosis in athletes: Where is the research? A systematic review. International Journal of Sports Physiology and Performance, 17(5), 675-681. https://doi.org/10.1123/ijspp.2021-0448